2006
DOI: 10.1097/01.brs.0000227326.35149.38
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Low Back Pain in Female Eldercare Workers: Randomized Controlled Work Site Trial

Abstract: The study showed no effect of a transfer technique or stress management program targeting LBP. Thus, there is a need for discussing other priorities in the prevention of LBP among health care workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 35 publications
0
44
0
Order By: Relevance
“…The effects seen in most studies were positive, with some of these being large and statistically significant (33,34,40,(46)(47)(48), others with size undetermined but statistically significant (49), and others more modest in size or non-significant (31)(32)(33). Two studies yielded small, negative effects (50,51). One of these (50) was statistically significant, but had poor internal validity, since there had been a major drop in the study sample size, which was distributed differently over the training and control groups.…”
Section: Effects Of Training On Behaviorsmentioning
confidence: 94%
See 1 more Smart Citation
“…The effects seen in most studies were positive, with some of these being large and statistically significant (33,34,40,(46)(47)(48), others with size undetermined but statistically significant (49), and others more modest in size or non-significant (31)(32)(33). Two studies yielded small, negative effects (50,51). One of these (50) was statistically significant, but had poor internal validity, since there had been a major drop in the study sample size, which was distributed differently over the training and control groups.…”
Section: Effects Of Training On Behaviorsmentioning
confidence: 94%
“…A second issue is apparent in the lack of knowledge and attitudes outcome data available to this review, relative to behaviors and health outcomes data -a surprising finding, given the typically greater ease of collecting knowledge and attitudes data. There were seven studies (33,40,49,51,58,65,66) that collected behavioral or health information pre-and postintervention by questionnaire. Some of these questionnaires could presumably have measured knowledge and attitudes too.…”
Section: Future Researchmentioning
confidence: 99%
“…Table 2 provides a brief summary of the six articles. The types of intervention were as follows: multidimensional method (Miyamoto et al, 1998 andSvensson et al, 2008); transfer technique and stress management (Jensen et al, 2006); lumbar support (Roelofs et al, 2007); stretching exercise (Kamioka et al, 2011); and cognitive behavioral theory (Menzel et al, 2006). In the main outcome measurement (for pain-relieving), it was only lumbar support that was statistically significantly effective (Svensson et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…A well designed RCT (Jensen et al, 2006) tried to evaluate the effectiveness of the Trans Technique Intervention (TTI ; Table 3) and the Stress Management Intervention (SMI; Table 4) in reducing LBP, but both program had no effect on LBP status after 2 years. The authors suggested that the important question remain as to whether the lack of improvement in low back health in the active intervention arms is caused by insufficient implementation of the interventions or if it is the intervention itself that failed to produce better low back health.…”
Section: Why Other Interventions Were Ineffectivementioning
confidence: 99%
“…Three countries in the European Union have national official manuals and guidance's for patient handling: Finland, Sweden and the UK [15]. To prevent low back disorders among nursing personnel, training programmes in patient transfer technique are common, most often comprising a theoretical basis and practical training [16,17,18,19,20,21,22,23]. Results from evaluation studies show an immediate improvement of work technique in transfer tasks among participants after taking part in a training programme [16,24,25].…”
Section: Introductionmentioning
confidence: 99%